An atom probe tomography study of the oxide–metal interface of an oxide intrusion ahead of a crack in a polycrystalline Ni-based superalloy. (1st March 2015) - Kitaguchi, H.S.; Moody, M.P.; Li, H.Y.; Evans, H.E.; Hardy, M.C.; Lozano-Perez, S.
Abstract : Intergranular oxide intrusions formed ahead of a crack in a Ni-based superalloy at 650 °C have been examined using three-dimensional atom probe tomography. Of two scans undertaken, a thin (∼5 nm) alumina layer was observed next to the alloy substrate in one, overlaid by a chromia layer. In the second, chromia penetrated to the alloy interface. The chromia layer contained Ti in solution as well as discrete particles of TiO2 .